Convergent recruitment of 5′‐hydroxylase activities by CYP75B flavonoid B‐ring hydroxylases for tricin biosynthesis in Medicago legumes. Issue 1 (27th March 2020) - Lui, Andy C. W.; Lam, Pui Ying; Chan, Kwun Ho; Wang, Lanxiang; Tobimatsu, Yuki; Lo, Clive
Summary: Tricin (3′, 5′‐dimethoxylated flavone) is a predominant flavonoid amongst monocots but occurs only in isolated and unrelated dicot lineages. Although tricin biosynthesis has been intensively studied in monocots, it has remained largely elusive in tricin‐accumulating dicots. We investigated a subgroup of cytochrome P450 (CYP) 75B subfamily flavonoid B‐ring hydroxylases (FBHs) from two tricin‐accumulating legumes, Medicago truncatula and alfalfa ( Medicago sativa ), by phylogenetic, molecular, biochemical and mutant analyses. Five Medicago cytochrome P450 CYP75B FBHs are phylogenetically distant from other legume CYP75B members. Among them, MtFBH‐4, MsFBH‐4 and MsFBH‐10 were expressed in tricin‐accumulating vegetative tissues. In vitro and in planta analyses demonstrated that these proteins catalyze 3′‐ and 5′‐hydroxylations critical to tricin biosynthesis. A key amino acid polymorphism, T492G, at their substrate recognition site 6 domain is required for the novel 5′‐hydroxylation activities. Medicago truncatula mtfbh‐4 mutants were tricin‐deficient, indicating that MtFBH‐4 is indispensable for tricin biosynthesis. Our results revealed that these Medicago legumes had acquired the tricin pathway through molecular evolution of CYP75B FBHs subsequent to speciation from other nontricin‐accumulating legumes. Moreover, their evolution is independent of that of grass‐specific CYP75B apigenin 3′‐hydroxylases/chrysoeriol 5′‐hydroxylases dedicated to tricin production and Asteraceae CYP75B flavonoid 3′, 5′‐hydroxylases catalyzing the production of delphinidin‐based pigments. Abstract : See also the Commentary on this article by Ralph, 228 : 11–14 .